Elaboración de cerveza artesanal de naranjilla (Solanum quitoense) y moringa (Moringa oleifera). - Corrales Alvarez, Jessica Liseth (2022)
The present research project has as aim to produce a moringa (Moringa Oleifera) and naranjilla (Solanum quitoense) craft beer with different concentrations, providing added value to the moringa and naranjilla use. At the country level and in the Cotopaxi province, it is identified a problem, what lies in the moringa productive use limited knowledge; into some cases, they use it as animal feed, and a large percentage, it is discarded, which it has been sought an use new alternative, through the craft beer elaboration. Into present research, it was made previous fermentation tests to determine moringa concentrations (2.4 g/L; 4.8 g/L and 7.2 g/L) and naranjilla (46.75 g/L; 93.5 g/L y 140.25 g/L), in order to know the variables behavior in the brewing process. For the elaboration, it proceeds with the raw material reception, then, to the maceration, subsequently, it proceed to the filtration; it continues with cooking and cooling by thermal shock; it goes to fermentation, and then, racking, packaging and maturation; at the end, it ends up in the final product storage. The experimental desing is performed, through a DBCA design with the Infostat program help, what allowed determining the best treatment based on sensory analysis, and once, got the best treatment, it was made a microbiological analysis, which presented the following results: bacteria count anaerobes <10 CFU/ml; mold count <10 CFU/ml; yeast counts 11x104 CFU/ml; in the physicochemical analysis is got the following results: alcoholic strength 3.40% V/V; pH 3.87; acidity 0.46% (lactic acid); carbonation 0.44 CO2 volumes, lead 0.21 mg/kg; arsenic <10 mg/kg; zinc <0.30 mg/kg; iron 15.03 mg/kg; copper <0.30 mg/kg; results, which are found within the alcoholic beverages NTE INEN 2263:2013 regulation.